1990
DOI: 10.1056/nejm199005313222205
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of a Geriatric Assessment Unit in a Community Rehabilitation Hospital

Abstract: We conducted a randomized trial in a community rehabilitation hospital to determine the effect of treatment in a geriatric assessment unit on the physical function, institutionalization rate, and mortality of elderly patients. Functionally impaired elderly patients (mean age, 78.8 years) who were recovering from acute medical or surgical illnesses and were considered at risk for nursing home placement were randomly assigned either to the geriatric assessment unit (n = 78) or to a control group that received us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(200 citation statements)
references
References 24 publications
6
192
0
2
Order By: Relevance
“…PADRECC is an integrated healthcare delivery model that uses a multidisciplinary assessment and management approach to PD. Both the VHA and the civilian sector have successfully implemented multidisciplinary approaches in the management of specific conditions, including amputation [1], age-related conditions [2][3], traumatic brain injury [4][5], diabetes mellitus [6], and stroke [7]. This investigation expands on an earlier study that assessed the impact of PADRECC multidisciplinary care on individuals with PD at 1-year follow-up [8].…”
Section: Introductionsupporting
confidence: 57%
“…PADRECC is an integrated healthcare delivery model that uses a multidisciplinary assessment and management approach to PD. Both the VHA and the civilian sector have successfully implemented multidisciplinary approaches in the management of specific conditions, including amputation [1], age-related conditions [2][3], traumatic brain injury [4][5], diabetes mellitus [6], and stroke [7]. This investigation expands on an earlier study that assessed the impact of PADRECC multidisciplinary care on individuals with PD at 1-year follow-up [8].…”
Section: Introductionsupporting
confidence: 57%
“…Numerous geriatric interventions have been developed to improve clinical outcomes for frail older adults (3)(4)(5)(6)(7). A major obstacle to the success of such interventions has been the absence of a standardized and valid method for screening of those who are truly frail so as to effectively target care (1,3).…”
mentioning
confidence: 99%
“…Randomised trial data show that geriatric rehabilitation programs increase the likelihood of patients returning to the community. 32 The relationship between rehabilitation program and functional gain in patients with cognitive impairment is complex. A systematic review showed benefi cial effects of a rehabilitation programme on physical function in cognitively impaired patients, 33 hence rehabilitation after hip fracture is mandatory even for cognitively impaired patients.…”
Section: Osteoporosis Managementmentioning
confidence: 99%